Incorporating innovation subsidies in the CDM framework: Empirical evidence from Belgium - Dirk Czarnitzki; Julie Delanote (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This paper integrates innovation input and output effects of R&D subsidies into a modified Crépon-Duguet-Mairesse (CDM) model. Our results largely confirm insights of the input additionality literature, i.e. public subsidies complement private R&D investment. In addition, results point to positive output effects of both purely privately funded and subsidy-induced R&D. Furthermore, we do not find evidence of a premium or discount of subsidy-induced R&D in terms of its marginal contribution on new product sales when compared to purely privately financed R&D.
urn:nbn:de:bsz:180-madoc-412327
Keywords: C14; C30; O38; 330; CDM model; R&D; subsidies; innovation policy